RESPONSIBILITY OF E-COMMERCE BUSINESS OPERATORS FOR SELF-PREFERENCING PRACTICES IN THE ABUSE OF DOMINANT POSITION - Hana Humaira Sachmaso; Heru Sugiyono (Awang Long Law Review, 2026)
Self-preferencing practices by dominant e-commerce platforms have distorted business competition by prioritizing internal products through algorithmic manipulation, limiting fair market access for third-party sellers and influencing consumer choice in a misleading way. Such conduct risks constituting an abuse of dominance and underscores the need for stronger transparency and nondiscrimination safeguards. This research aims to analyze the qualification of self-preferencing as a form of abuse of dominant position and the legal liability of business actors in Indonesia. The research method employed is normative juridical with statutory and case comparison approaches, specifically examining the law enforcement against Coupang in South Korea. The results indicate that although not explicitly regulated, self-preferencing fulfills the elements of discrimination under Article 19 letter d and Article 25 of Law No. 5 of 1999. However, the KPPU case study on Shopee demonstrates that law enforcement remains limited to behavioral remedies mechanisms due to challenges in proving algorithmic conduct. Beyond competition law, the non-discrimination principle is also a liability for business actors based on the ITE Law and Government Regulation No. 80 of 2019. This study concludes the necessity for explicit regulation regarding algorithmic transparency and self-preferencing in Indonesia, reflecting on the strict guidelines applied in South Korea, to ensure a fair digital ecosystem.